Isobaric Critical Exponents: Test of Analyticity Against NIST Reference Data - Cho, Wonyoung; Kim, Do-Hyun; Park, Jeong-Hyuck (Frontiers in Physics, 2018)
Finite systems may undergo first or second order phase transitions under not isovolumetric but isobaric condition. The `analyticity' of a finite-system partition function has been argued to imply universal values for isobaric critical exponents, α_P, β_P and γ_P. Here we test this prediction by analyzing NIST REFPROP data for twenty major molecules, including H_2O, CO_2, O_2, etc. We report they are consistent with the prediction for temperature range, 10^-5 <|T/T_c-1|<10^-3. For each molecule, there appears to exist a characteristic natural number, n=2,3,4,5,6, which determines all the critical exponents for T<T_c as α_P=γ_P=nn+1 and β_P=δ^-1=1n+1. For the opposite T>T_c, all the fluids seem to indicate the universal value of n=2.